2022
DOI: 10.12911/22998993/143866
|View full text |Cite
|
Sign up to set email alerts
|

Seed Quality and Protein Classification of Some Quinoa Varieties

Abstract: Quinoa plants, originating from the Andean mountains in South America, have a large scale of biological diversity. Along with the cultivation favorableness of quinoa, it reveals superior nutrition aspects. In comparison with cereal crops, like rice, maize, and wheat, quinoa seeds contain valuable quantities of protein of remarkable quality. The current study compared four quinoa cultivars from different origins in terms of protein composition and germinability. In addition, this study focused on the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Research focused on gene expression and regulation includes hybridization (Hodková & Mandák, 2018), phylogenetic (Li et al, 2022), and proteomic studies in relation to edaphoclimatic factors where cultivars are grown (Zhao et al, 2022). The main objective of genic expression studies has been to find the relationship between the agri-environmental offer and the genetic variability associated with the greater production of seeds with high contents of vegetable proteins (El-Hakim et al, 2022) and high-value biocomposites (Campos-Rodriguez et al, 2022). This is consistent with what was reported by and García-Parra, Zurita-Silva, et al (2020), who indicated that the environmental temperature plays an important role in the phenological phases prior to the development of the seed, influencing productive and compositional aspects.…”
Section: Green Cluster (89 Key Topics)-genic Expressionmentioning
confidence: 99%
“…Research focused on gene expression and regulation includes hybridization (Hodková & Mandák, 2018), phylogenetic (Li et al, 2022), and proteomic studies in relation to edaphoclimatic factors where cultivars are grown (Zhao et al, 2022). The main objective of genic expression studies has been to find the relationship between the agri-environmental offer and the genetic variability associated with the greater production of seeds with high contents of vegetable proteins (El-Hakim et al, 2022) and high-value biocomposites (Campos-Rodriguez et al, 2022). This is consistent with what was reported by and García-Parra, Zurita-Silva, et al (2020), who indicated that the environmental temperature plays an important role in the phenological phases prior to the development of the seed, influencing productive and compositional aspects.…”
Section: Green Cluster (89 Key Topics)-genic Expressionmentioning
confidence: 99%
“…In recent years, the cultivation of plants such as quinoa and amaranth has received increased attention due to the high nutritional value of these species (Abd El‐Hakim et al., 2022). Quinoa ( Chenopodium quinoa Willd.)…”
Section: Introductionmentioning
confidence: 99%
“…Quinoa, a significant pseudo-cereal, is renowned for its ability to withstand environmental stress and its high nutritional content, making it a widely advocated cultivar for human consumption and nutrition [5]. Native to South America's Andean mountains, quinoa exhibits a wide range of biological diversity, as highlighted by Abd El-Hakim et al [6]. Notably, quinoa is considered a complete food with attractive nutritional value, boasting a high level of high-quality protein that surpasses rice and wheat [7].…”
Section: Introductionmentioning
confidence: 99%